ChemInform Abstract: Facile Synthesis of Densely Substituted Chroman Derivatives Through Broensted Acid Ionic Liquid Catalyzed Three‐Component Reactions of Aromatic Aldehydes, 1, 1‐Diarylethylenes and Nucleophiles. Issue 20 (April 2016) - Taheri, Amir; Lai, Bingbing; Yang, Jing; Zhang, Juan; Gu, Yanlong
Abstract: Broensted acid ionic liquid‐catalyzed two‐ and three‐component reactions leading to chroman derivatives are presented.